Identification of C-Kit-Positive Interstitial Cells in the Dog Lower Urinary Tract and Relationship with Smooth Muscle and Nerves. Hypotheses for a Likely Pacemaker Role. - Silvana Arrighi; Giampaolo Bosi; Debora Groppetti; Fausto Cremonesi (Veterinary Medicine International)
The aim of this work was to give an evidence of the likely presence of interstitial cells in the canine lower urinary tract and to study their possible interactions with the musculature and the intramural innervation. Cryosections of normal canine bladder and urethra were immunofluorescently labelled with c-kit, a transmembrane, tyrosine kinase growth factor receptor, known to be expressed on the interstitial cells of Cajal (ICCs) of the gut. The relationship with antiactin positive smooth muscle cells and PGP9.5-positive intramural innervation was also investigated by confocal microscopy. Anti-c-kit labelling demonstrated a network of elongated and branched c-kit positive cells, which were located in interstitial spaces, oriented in parallel to the smooth muscle bundles that form the bladder muscular layer, irrespective of dog sex. Cells with a similar localization were also PAS- and NADPH-diaphorase-positive. A contact between c-kit immunofluorescent cells and intramural innervation was demonstrated, too. The roles of interstitial cells might include regulation of smooth muscle activity of the bladder detrusor, integrating neuronal signals during urine storage and voiding.